Chambers dictionary of beliefs and religions - Vernon, Mark, 1966- (Edinburgh : Chambers, 2009)
Even in our high-tech world, billions of people continue to place their faith in a god, or gods, in spirits or in another form of divinity. Many adhere to beliefs outside the major faith traditions, while others see science and secular modernity as providing a sufficient basis for a meaningful life.
Contents note continued: Sociology of religion -- Women in religions -- Experience of Religion -- Ablutions -- Almsgiving -- Death -- Doubt and belief -- Family -- Food and drink -- Funerary practices -- Happiness -- The meaning of life -- Meditation -- Prayer -- Retreats -- Sacred places -- Spirituality and religion -- Places of Worship -- Visiting a Buddhist temple -- Visiting a Christian church -- Visiting a Hindu temple -- Visiting a Mosque -- Visiting a Sikh Gurudwara.
Formerly CIP.
Keywords: Religions -- Dictionaries